Impact of an early respiratory care programme with non‐invasive ventilation adaptation in patients with amyotrophic lateral sclerosis. (29th January 2018) - Vitacca, M.; Montini, A.; Lunetta, C.; Banfi, P.; Bertella, E.; De Mattia, E.; Lizio, A.; Volpato, E.; Lax, A.; Morini, R.; Paneroni, M.; ,
Abstract : Background and purpose: Forced vital capacity (FVC) <80% is one of the key indications for starting non‐invasive ventilation (NIV) in amyotrophic lateral sclerosis (ALS). It was hypothesized that a very early start of NIV could lengthen the free interval before death compared to later‐start NIV; as a secondary outcome, the survival rate of patients on NIV without tracheotomy was also evaluated. Methods: This retrospective study was conducted on 194 ALS patients, divided into a later group (LG) with FVC <80% at NIV prescription ( n = 129) and a very early group (VEG) with FVC ≥80% at NIV prescription ( n = 65). Clinical and respiratory functional data and time free to death between groups over a 3‐year follow‐up were compared. Result: At 36 months from diagnosis, mortality was 35% for the VEG versus 52.7% for the LG ( P = 0.022). Kaplan−Meier survival curves adjusted for tracheotomy showed a lower probability of death ( P = 0.001) for the VEG as a whole ( P = 0.001) and for the non‐bulbar (NB) subgroup ( P = 0.007). Very early NIV was protective of survival for all patients [hazard ratio (HR) 0.45; 95% confidence interval (CI) 0.28–0.74; P = 0.001] and for the NB subgroup (HR 0.43; 95% CI 0.23–0.79; P = 0.007), whilst a tracheotomy was protective for all patients (HR 0.27; 95% CI 0.15–0.50; P = 0.000) and both NB (HR 0.26; 95% CI 0.12–0.56; P = 0.001) and bulbar subgroups (HR 0.29; 95% CI 0.11–0.77; P = 0.013). Survival in VEG patients on NIV without tracheotomy was three times that for the LG (43.1% vs. 14.7%). Conclusion: Very early NIV prescription prolongs the free time from diagnosis to death in NB ALS patients whilst tracheotomy reduces the mortality risk in all patients.